Review of Chaotic Based S-Box Structures - Cengiz, Ayse; Avci, Derya (Ieee, 2019)
The design of the S - box is important to ensure immediate security at the attack. System security increases when s-box systems are formed with a chaotic base. In this paper, the methods used to create chaotic based s-boxes were investigated and a literature study was conducted.
7th International Symposium on Digital Forensics and Security (ISDFS) -- JUN 10-12, 2019 -- Barcelos, PORTUGAL
Keywords: S-box; Chaotic; Security; Cryptology